Analisis Pengaruh Harga dan Biaya Promosi Terhadap Tingkat Penjualan Batik Pada Koperasi Komunitas Batik Bekasi - Reni Yesi; Widia (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
This study aims to determine and analyze how much influence price and promotion costs have on the sales level of batik from the Bekasi Batik Community Cooperative (KOMBAS). Data analysis techniques using multiple linear regression analysis, multiple linear correlation analysis, t test analysis and f test analysis. The results of multiple linear regression analysis show that there is an effect of price and promotion costs on the sales level of the Bekasi batik community cooperative (KOMBAS), where the value of the regression analysis is Y = 2,071 + 8,054(X1) + 16,260(X2). That is, if there is no increase in price and promotion costs (X1 = 0 and X2 = 0) then sales will decrease by 2,071. Based on the results of calculations using the multiple linear correlation formula between the effect of price (X1) on sales (y), a result of 68% is obtained, the results show that there is an influence between price (X1) and the level of sales (y). Then based on the results of calculations using the multiple correlation coefficient formula between promotional costs (X2) and sales levels (y), the results obtained are 85%, these results show that there is a significant relationship between promotional costs (X2) and sales levels (y). Based on the results of calculations using the multiple linear correlation coefficient formula, it shows that there is a relationship between the effect of price and promotion costs on the level of batik sales at the Bekasi batik community cooperative (KOMBAS) of 85%. Then on the results of the coefficient of determination there is a result of 73%. And from the results of the hypothesis testing, it is calculated that TcountX1y = 5.3589 while TcountX2y = 13.5916 and Ttable = 2.10092 according to the above provisions, if tcount > ttable, it can be concluded that Ho is rejected and Ha is accepted, which means that there is a significant influence means between price and promotion costs to the level of sales. From the results of the calculation of the Fcount test 24.5333 ? Ftable 3.59 means that there is a simultaneous or simultaneous influence between the effect of price and promotion costs on the sales level of the Bekasi batik community cooperative (KOMBAS).